Pengaruh Literasi Keuangan, Gaya Hidup dan Pengendalian Diri terhadap Perilaku Konsumtif dalam Islam Pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Thaha Saifuddin Jambi - Rina Hartati; Elyanti Rosmanidar; Yuliana Safitri (Journal of Student Research, 2023)
There are still many FEBI students UIN STS Jambi who do not understand Financial Literacy, so they often allocate their money for things that are not needed. Lifestyle patterns lead to consumptive behavior. Self-control is still relatively low so it is easy to be influenced to buy something that is not needed. Research objectives determine the effect of financial literacy, lifestyle and self-control on consumptive behavior in Islam. This research used quantitative research. Quantitative research method is a method based on philosophy that is used to research certain populations and samples, data collection uses research instruments, analysis is quantitative or statistical, with the aim of testing the hypotheses that have been set. Lifestyle influences consumptive behavior. But financial literacy and self-control have no effect on consumptive behavior, which means that even without financial literacy and self-control, students still behave consumptively. but simultaneously Financial Literacy, Lifestyle and Self-Control affect Consumptive Behavior. FEBI students UIN STS JAMBI are expected to improve their financial literacy, lifestyle and self-control so they can avoid consumptive behavior. Future researchers are expected to be able to use other variables besides Financial Literacy, Lifestyle and Self-Control to show other things that also influence the level of Consumptive Behavior.